ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN GOOD GOVERNANCE PADA PEMERINTAH PROVINSI BALI - Ayub, Rai Devia; Suyana Utama, Made; Wardana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018, 2018)
The implementation of good governance is a prerequisite for the government in realizing the aspirations of the people and achieving the ideals of the nation and state. After a review of the external and internal audit results, there is a tendency to increase the number of recommendations given to the findings of the examination results. Recommendations are given by external and internal auditors in the framework of improvement and follow-up on the findings of examinations. This study analyzed the direct and indirect influence between the variables of Regional Financial Management, SPIP, SAKIP, and Good Governance in Bali Provincial Government by using primary data of quantitative in the form of associative supported by secondary data. Analytical techniques are descriptive and alternative structural equations of SEM PLS. The results showed that the variable of Regional Financial Management and SPIP have a positive and significant effect on SAKIP with R-Square value of 0.647. In addition, the variables of Regional Financial Management, SPIP, SAKIP also have a positive and significant effect on Good Governance with R-Square value of 0.784.